The cat who sniffed glue - Braun, Lilian Jackson (Jove Books, 1989)
Having inherited millions, Jim Qwilleran and his two feline companions, Koko and Yum Yum, are preparing to settle down into a life of purrfect luxury in Pickax. That is, until the son of a rich banker and his wife are found murdered. To the police it looks like a robbery gone awry. But then Koko develops an odd appetite for glue. Qwill doesn<U+2019>t spot the clue until his beloved Siamese<U+2019>s taste for paste tangles them in a web of love, danger, and their stickiest case yet!